Combinination Essential Ginger Oil and Acupressure Relaxation Techniques to Nausea and Vomiting - Lisnawati, Ketut; Wati, Ni Made Nopita; Ni Luh Putu Thrisna Dewi; A.A Sri Sanjiwani (Basic and Applied Nursing Research Journal, 2024)
Introduction: Nausea and vomiting are effects of chemotherapy that can decrease in the health condition of cancer patients. Objective: The aim of this study was to determine the effect of the combination of essential ginger oil therapy and acupuncture relaxation techniques on nausea and vomiting in cancer patients undergoing chemotherapy. Methods: This research used a quasi-experimental design. The population of this study was 124 adults undergoing chemotherapy. Sampling used purpose-based sampling with a sample size of 34 respondents (17 people in the treatment group and 17 people in the control group). Nausea and vomiting were measured using the Rhodes Index Nausea, Vomitting and Retching instrument. Results: The study results showed that before receiving the intervention, the intervention group's nausea and vomiting score averaged around a score of 6, in the control group the mean score was around 6. After the intervention, the nausea and vomiting score of the intervention group was 2, in the control group 10. The Wilcoxon test showed a significant value (p < 0.001). Conclusion: The combination of essential ginger oil and Acupressure relaxation techniques helped to reduce nausea and vomiting due to chemotherapy in cancer patients. This means that an intervention given regularly can educe nausea and vomiting. Oncology nurses could give recommendation to the hospital to provide this intervention to the chemotherapy patients.